2013
DOI: 10.1044/1092-4388(2012/11-0184)
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Sentence Length and Syntactic Complexity on the Speech Motor Control of Children Who Stutter

Abstract: Purpose To investigate the potential effects of increased sentence length and syntactic complexity on the speech motor control of children who stutter (CWS). Method Participants repeated sentences of varied length and syntactic complexity. Kinematic measures of articulatory coordination variability and movement duration during perceptually fluent speech were analyzed for 16 CWS and 16 typically developing children (CTD) between 4 and 6 years of age. Behavioral data from a larger pool of children were also ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 48 publications
4
59
2
Order By: Relevance
“…Walsh et al (2015) reported that in short, simple sentence production (e.g., "buy bobby a puppy"), relative to their typically fluent 4-and 5-year-old peers, CWS lagged in speech motor coordination and in measures of basic kinematic parameters, such as articulatory speed. In addition, in an experimental paradigm identical to the one employed in the current study with sentences of varying length and complexity, 4-to 6-year-old CWS exhibited increased lip aperture variability (LAVar) compared to children who do not stutter (CWNS) for fluent productions (MacPherson & Smith, 2013). Such results suggest that CWS in the preschool years lag behind their peers in speech motor development.…”
mentioning
confidence: 68%
See 4 more Smart Citations
“…Walsh et al (2015) reported that in short, simple sentence production (e.g., "buy bobby a puppy"), relative to their typically fluent 4-and 5-year-old peers, CWS lagged in speech motor coordination and in measures of basic kinematic parameters, such as articulatory speed. In addition, in an experimental paradigm identical to the one employed in the current study with sentences of varying length and complexity, 4-to 6-year-old CWS exhibited increased lip aperture variability (LAVar) compared to children who do not stutter (CWNS) for fluent productions (MacPherson & Smith, 2013). Such results suggest that CWS in the preschool years lag behind their peers in speech motor development.…”
mentioning
confidence: 68%
“…We predicted that CWS-Per would likely exhibit higher LAVar, but not longer movement duration, compared to CWSRec and CWNS, on the basis of findings from previous studies (MacPherson & Smith, 2013;Walsh et al, 2015). We also hypothesized that increasing linguistic complexity would have a disproportionate effect on the speech motor systems of CWS-Per compared to our other two groups.…”
Section: Purpose Of the Studymentioning
confidence: 91%
See 3 more Smart Citations